2016
DOI: 10.1021/acs.jpcb.6b11773
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Photochemical Reaction Pathways of Tungsten Hexacarbonyl in Solution from Femtoseconds to Minutes

Abstract: Metal-organic complexes are widely used across disciplines for energy and biological applications, however, their photophysical and photochemical reaction coordinates remain unclear in solution due to pertaining molecular motions on ultrafast time scales. In this study, we apply transient absorption and tunable femtosecond stimulated Raman spectroscopy (FSRS) to investigate the UV photolysis of tungsten hexacarbonyl and subsequent solvent binding events. On the macroscopic time scale with UV lamp irradiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…Subsequent isomerization to the thermodynamically preferred O-bound form then occurred. Although such an η 2 -C–H/O rearrangement process has previously been proposed on the basis of transient absorption spectroscopy, the use of, the more structurally informative, TRIR has allowed for the precise nature of the metal–solvent interactions to be probed and discerned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent isomerization to the thermodynamically preferred O-bound form then occurred. Although such an η 2 -C–H/O rearrangement process has previously been proposed on the basis of transient absorption spectroscopy, the use of, the more structurally informative, TRIR has allowed for the precise nature of the metal–solvent interactions to be probed and discerned.…”
Section: Discussionmentioning
confidence: 99%
“…Gaining such insight is challenging as the solvation event and resulting dynamics are extremely rapid in many systems. For example, previous studies on complexes M­(CO) 6 (M = Cr, Mo, and W) have demonstrated that the photochemically induced loss of CO to form putative M­(CO) 5 occurs within 100 fs, and the subsequent solvation event is occurring between 1 and 3 ps which depends also on the solvent employed . Although, there are examples in which CO dissociation occurs over longer (ps) time scales. Time-resolved spectroscopy, in which the photochemical activation of a thermally inert substrate acts as a trigger for the spectroscopic probe, provides an excellent tool to investigate this problem.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, femtosecond stimulated Raman spectroscopy (FSRS) has become a powerful spectroscopic methodology that can provide the equilibrium and non-equilibrium vibrational signatures and track excited-state molecular dynamics with simultaneously high spectral and temporal resolutions [1][2][3][4][5][6][7]. Over recent years, a great variety of chemically and biologically relevant systems have been studied by FSRS spanning from organic photoacids and chromophores [8][9][10][11][12][13][14][15], molecular rotors [16], fluorescent proteins [3,17], photoreceptor proteins [18][19][20][21][22][23][24][25][26], calcium biosensors [4,[27][28][29], metal complexes [30,31], materials [32][33][34], and engineered molecular systems [35,36]. The underlying photophysical and photochemical processes including excited-state proton transfer, charge transfer, vibrational cooling, internal conversion, isomerization, and bond dissociation have been successfully revealed and discussed in the larger context of effectively delineating the structure-energy-function relationships [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The best results were obtained when the solution was stirred for 1 h prior to deposition, which leads to a partial CO ligand exchange to coordinated methanol triggered by UV light. 33 The SEM image in Figure 1a clearly illustrates the formation of tungsten oxide NWs in the process and shows that these NWs can be grown on site-selectively heated areas in a cold-wall reactor. Fine-tuning of the deposition temperature allows the exclusive formation of NWs, without a particle codeposit on the membranes and NWs (Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We achieved site-selective growth of tungsten oxide NWs exclusively in the heated area of a micromembrane by aerosol assisted CVD using a methanol solution of tungsten hexacarbonyl. The best results were obtained when the solution was stirred for 1 h prior to deposition, which leads to a partial CO ligand exchange to coordinated methanol triggered by UV light . The SEM image in Figure a clearly illustrates the formation of tungsten oxide NWs in the process and shows that these NWs can be grown on site-selectively heated areas in a cold-wall reactor.…”
Section: Resultsmentioning
confidence: 99%